Mestrado em Engenharia de Produção da UFAM: contribuições e desafios para o desenvolvimento da engenharia de produção no Estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The Professional Master in Production Engineering at UFAM has an important role in the technological, economic, and social development of the northern region. CAPES seeks to evaluate the effectiveness and quality of the insertion of new masters in the academic environment and the impact on society of the knowledge obtained. In this sense, this work aims to analyze the contributions of the Professional Master's course in Production Engineering at UFAM to the development of the area and its future challenges. To achieve the proposed objective, quantitative and qualitative research was carried out, of a descriptive nature and based on data collected through a questionnaire and semi-structured interviews. The results of the research indicate that contributions are generated both for the graduates from the improvement in their professional situation, for the organizations through the implemented researches that generate local and regional development, and for the academy through terms of partnerships to empower these professionals. The study points out that, although the research has identified that the graduates sought participation in events, the program has weaknesses about the qualification and quantity of scientific productions carried out by both students and teachers, a fundamental requirement to raise a superior concept with CAPES.
Keywords: Engenharia de produção - Pós-graduação - Manaus (AM); ENGENHARIAS; Mestrado profissional; Engenharia de Produção; Perfil do Egresso; Indicadores de Produtividade